(untitled) - Conklin, John E. (New York, 1981)
This text in criminology covers topics such as crime on campus, crime in cross-cultural perspective, and using criminology. It contains sections on gender, feminist criminology and power-control theory. This edition includes an expanded section on the social organization of white-collar crime.
Keywords: Criminology